Structural determinants of ligand binding in the ternary complex of human ileal bile acid binding protein with glycocholate and glycochenodeoxycholate obtained from solution NMR. (4th January 2016) - Horváth, Gergő; Bencsura, Ákos; Simon, Ágnes; Tochtrop, Gregory P.; DeKoster, Gregory T.; Covey, Douglas F.; Cistola, David P.; Toke, Orsolya
Abstract : Besides aiding digestion, bile salts are important signal molecules exhibiting a regulatory role in metabolic processes. Human ileal bile acid binding protein (I‐BABP) is an intracellular carrier of bile salts in the epithelial cells of the distal small intestine and has a key role in the enterohepatic circulation of bile salts. Positive binding cooperativity combined with site selectivity of glycocholate and glycochenodeoxycholate, the two most abundant bile salts in the human body, make human I‐BABP a unique member of the family of intracellular lipid binding proteins. Solution NMR structure of the ternary complex of human I‐BABP with glycocholate and glycochenodeoxycholate reveals an extensive network of hydrogen bonds and hydrophobic interactions stabilizing the bound bile salts. Conformational changes accompanying bile salt binding affects four major regions in the protein including the C/D, E/F and G/H loops as well as the helical segment. Most of these protein regions coincide with a previously described network of millisecond time scale fluctuations in the apo protein, a motion absent in the bound state. Comparison of the heterotypic doubly ligated complex with the unligated form provides further evidence of a conformation selection mechanism of ligand entry. Structural and dynamic aspects of human I‐BABP–bile salt interaction are discussed and compared with characteristics of ligand binding in other members of the intracellular lipid binding protein family. Protein Data Bank Accession Numbers: The coordinates of the 10 lowest energy structures of the human I‐BABP : GCDA : GCA complex as well as the distance restraints used to calculate the final ensemble have been deposited in the Brookhaven Protein Data Bank with accession number2MM3 . Abstract : Human ileal bile acid‐binding protein (hI‐BABP) has a key role in the enterohepatic circulation of bile salts. Solution NMR structure of the ternary complex of hI‐BABP with glycocholate and glycochenodeoxycholate reveals a network of hydrogen bonds and hydrophobic interactions stabilizing the bound bile salts. Comparison of the complex with the unligated form indicates a conformation selection mechanism of ligand entry.